Trends and Tourists Purchasing Interest at The Souvenir Center of The Ragunan Zoo Wildlife Park - Setyawati, Irma; Nugraha, Rizki Nurul (West Science Social and Humanities Studies, 2024)
This research focus on trend analysis and tourists’ purchasing interest at souvenir center of the Ragunan zoo wildlife park. The research title chosen because souvenir center have has attraction potential that significant for visitors. and understanding factors that influence purchasing interest and tourists trend can provide the important insights for souvenir center management. Methodology that used is qualitative descriptive with analytical approach SWOC, involving observation and literature review. Problem Formulation includes an understanding of economic factor, social motives, that influence purchasing interest, impact of Anggrek park Ragunan to the trends of ornamental plant collection trends, and SWOC analysis to identify strengths, weakness, opportunities, and challenges in Ragunan souvenir center. This research aims to provide contribution to improve management and interest of souvenir product at this tourist destination.